2019
DOI: 10.3390/microorganisms7070194
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Lactobacillus fermentum CQPC05 Isolated from Sichuan Pickle in High-Fat Diet-Induced Obese Mice through PPAR-α Signaling Pathway

Abstract: Sichuan pickle is a traditional fermented food in China which is produced by the spontaneous fermentation of Chinese cabbage. In this study, the anti-obesity effects of a new lactic acid bacterium (Lactobacillus fermentum CQPC05, LF-CQPC05) isolated from Sichuan pickles were assessed in vivo. An obese animal model was established in mice by inducing obesity with high-fat diet. Both serum and tissues were collected from the mice, and then subjected to qPCR and Western blot analyses. The results showed that LF-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
4
34
0
Order By: Relevance
“…These indicators will be obviously abnormal in the case of liver damage. Those with abnormal liver function cannot metabolize fat normally, which leads to obesity (Zhu et al, 2019). This study again proves that LF-CQPC04 can regulate lipid metabolism and ease liver dysfunction caused by abnormal lipid levels.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These indicators will be obviously abnormal in the case of liver damage. Those with abnormal liver function cannot metabolize fat normally, which leads to obesity (Zhu et al, 2019). This study again proves that LF-CQPC04 can regulate lipid metabolism and ease liver dysfunction caused by abnormal lipid levels.…”
Section: Discussionsupporting
confidence: 57%
“…The liver tissue was homogenized with a tissue homogenizer, and the tissue homogenate was obtained from the upper layer after centrifugation (4000 rpm/min for 10 min). Serum and tissue homogenate indicators were measured according to the kit instructions (Nanjing Jiancheng Bioengineering Institute, Nanjing, China) (Zhu et al, 2019).…”
Section: Determination Of Tg Tc Hdl-c Ldl-c Akp Ast and Alt Levmentioning
confidence: 99%
“…Previous studies on different diet or materials regulating lipid metabolism indicated that the changes of plasma HDL cholesterol level and para-and perirenal fat content always inconsistent. For example, Lactobacillus fermentum CQPC05 isolated from Sichuan pickles could decrease perirenal fat index in high-fat diet mice, meanwhile plasma HDL cholesterol level reduced obviously [18]. Low dose doxycycline treated 6-week-old male db/db mice for 10 weeks showed that perirenal/epididymal fat index, and liver cholesterol reduced, but blood HDL cholesterol level increased [19].…”
Section: Discussionmentioning
confidence: 99%
“…One study in obese patients found that perirenal fat thickness was lower and HDL cholesterol was higher after sleeve-gastrectomy surgery [17]. While another study in obese animal found the contrary results [18]. Based on the above background, this study aimed to explore the relationship between para-and perirenal fat and serum HDL level and cholesterol efflux capacity in patients with T2DM.…”
Section: Introductionmentioning
confidence: 98%
“…Modern experiments have shown that natural plants have a wide range of biological effects and these effects are closely related to the cytokine network. 23 IL-10 plays multiple roles in the regulation of tumor immunity, inflammatory response, and autoimmune response. It can stimulate T cells, especially CD8 + cells; stimulate B cells to mature, proliferate, and generate antibodies; and increase the ability of killing tumor cells.…”
Section: Discussionmentioning
confidence: 99%